110k views
5 votes
Let f(x) = 2x^2 + x - 3 and g(x) = x+ 2. Find (f • g) (x)

User Numzero
by
4.4k points

1 Answer

4 votes

Answer:

(f • g) (x) = 2x² + 9x + 7

Explanation:

f(x) = 2x² + x - 3

g(x) = x + 2

To find (f • g) (x) substitute g(x) into every x in f (x)

That's

(f • g) (x) = 2(x + 2)² + x + 2 - 3

Expand and simplify

(f • g) (x) = 2( x² + 4x + 4) + x - 1

= 2x² + 8x + 8 + x - 1

Group like terms

= 2x² + 8x + x + 8 - 1

We have the final answer as

(f • g) (x) = 2x² + 9x + 7

Hope this helps you

User Dharmesh Vaghani
by
5.6k points